2023
DOI: 10.1186/s40249-023-01110-2
|View full text |Cite
|
Sign up to set email alerts
|

What are the pathways between poverty and malaria in sub-Saharan Africa? A systematic review of mediation studies

Abstract: Background Malaria remains a major burden in sub-Saharan Africa (SSA). While an association between poverty and malaria has been demonstrated, a clearer understanding of explicit mechanisms through which socioeconomic position (SEP) influences malaria risk is needed to guide the design of more comprehensive interventions for malaria risk mitigation. This systematic review provides an overview of the current evidence on the mediators of socioeconomic disparities in malaria in SSA. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…In previous studies, it was also shown that low SES was an important risk factor for malaria infections [ 45 , 58 60 ], mainly due to the strong association between malaria and poverty [ 61 , 62 ]. Poor people have a higher risk of malaria infections because they cannot afford the cost of malaria prevention and/or treatment and they lack and/or possess a low level of knowledge and skills required to protect themselves against malaria infections [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, it was also shown that low SES was an important risk factor for malaria infections [ 45 , 58 60 ], mainly due to the strong association between malaria and poverty [ 61 , 62 ]. Poor people have a higher risk of malaria infections because they cannot afford the cost of malaria prevention and/or treatment and they lack and/or possess a low level of knowledge and skills required to protect themselves against malaria infections [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, poverty which was identified as a keyfactors for non-adherence to HIV treatment had also been cited in the literature on several other health conditions in sub-Saharan Africa as inhibitory especially as it relates to procurement of drugs and cost of transportation to facilities. In the case of malaria for instance, poverty has been linked to inadequate housing, low education, poor nutrition and non-use of insecticide treated nets among others (Wafula, Habermann, Franke, May, Puradiredja et al, 2023). However, the unique thing about nonadherence to HIV medication is the danger of relapsing and loss of the gains made in viral suppression over time.…”
Section: Discussionmentioning
confidence: 99%